Proteomic analysis on host responses to Chikungunya virus infection / Christina Thio Li Ping - Thio, Christina Li Ping (2013)
Chikungunya virus (CHIKV) is an arthropod-borne virus that has caused multiple unprecedented outbreaks in both tropical and temperate countries over the past five decades. There is no commercial vaccine or antiviral drug to date, due in part to the lack of knowledge and understanding of the biology and pathogenesis of this virus. Thus, there is an increasing need for researchers to focus their research efforts in this area of virology. The current study employed proteomics to investigate alterations of the whole cell proteome and secretome of WRL-68 cells during early CHIKV infection, with the main aim being to identify the key proteins modulated in response to infection. Two-dimensional gel electrophoresis (2-DGE) was used to compare the whole cell proteome and secretome profiles between mock control cells and cells infected at the optimised multiplicity of infection (MOI) of 5.0 at 24 hours post-infection. Protein spots that were found to be differentially expressed were identified by MALDITOF/ TOF mass spectrometry (MS) analysis, and three selected proteins were validated by Western blot. The functional association between these proteins were determined by STRING network analysis, and the mRNA expression level of selected proteins was investigated via real-time quantitative PCR. Overall, 50 and 25 protein spots from the whole cell proteome and secretome samples, respectively, were found to be differentially expressed (fold-change > 1.3, p < 0.05) and were successfully identified. The mRNA expression of 15 whole cell proteins was found to correlate with the corresponding protein expression. On the contrary, only one of the 15 selected proteins from the secretome sample showed positive correlation with its transcript expression level. By combining the proteomics and bioinformatics data from STRING network analysis, it was deduced that CHIKV disrupt the overall host cell metabolic machinery and ubiquitin-proteasome pathway (UPP). Suppression of the host immune response was also observed through the inhibition of immune-related protein secretion, mainly ii cathepsin D, cathepsin L1, C3 protein and β-2 microglobulin. Several gene expressionrelated proteins were also down-regulated, including the mRNA processing factor, hnRNP E1, and translational factors, namely elongation factor-2, eukaryotic initiation factor eIF-2BA and eIF3 subunit H. Meanwhile, up-regulation of hnRNP C1/C2 suggests that this protein may be beneficial to CHIKV. Cell cycle regulation via cyclindependent kinase 1 (CDK1) activity may also play an important role during early CHIKV infection. CDK1 was down-regulated, whereas several other proteins (such as SET protein) that indirectly regulate the activity of CDK1, were altered in favour of the inhibition of CDK1 activity. In conclusion, CHIKV infection in the human liver cells induced a widespread alteration of the whole cell proteome and secretome. Nevertheless functional characterisations of these proteins are entailed to provide more insights into the actual mechanisms at play during early infection.